PERFORMANCE OF NATIVE GOATS IN KURDISTAN REGION OF IRAQ: A REVIEW - Jalal Alkass; Kamal Mustafa (Mesopotamia Journal of Agriculture)
Two breeds of goats are native to Kurdistan region- Iraq, namely mountainous black goat is raised mainly for meat and milk production, and Meriz which is raised primarily for hair beside meat and milk. The two breeds were exposed over a long period of time to the vigorous and sever semi-dry conditions, drought, feed shortage and prevailing diseases. Hence their adaptation to such conditions was at the expense of important economic traits. From the limited work available for both breeds, it seems that Meriz characterized by smaller size than did black goat, and daily gain in weight is rather low for the two breeds being 0.068-0.140 kg. it seems that black goat in particular have a potential for improvement of milk yield because display over whelming range (127-189 L.). In general, fertility and prolificacy are rather low in black goat and an improvement of the reproductive performance was achieved by hormonal treatment and /or flushing and studies on semen traits revealed that bucks are seasonal breeders especially in Meriz. However, the two breeds are not well characterized and much work is needed to explore the potential of those breeds for economic traits.